2018
DOI: 10.1074/jbc.ra117.001150
|View full text |Cite
|
Sign up to set email alerts
|

Histone variant H3.3–mediated chromatin remodeling is essential for paternal genome activation in mouse preimplantation embryos

Abstract: Derepressionof chromatin-mediated transcriptional repression of paternal and maternal genomes is considered the first major step that initiates zygotic gene expression after fertilization. The histone variant H3.3 is present in both male and female gametes and is thought to be important for remodeling the paternal and maternal genomes for activation during both fertilization and embryogenesis. However, the underlying mechanisms remain poorly understood. Using our H3.3B-HA-tagged mouse model, engineered to repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 52 publications
(105 reference statements)
0
35
0
Order By: Relevance
“…Although present in both sperm and egg, paternally derived H3.3 is lost after fertilization (Kong et al, 2018). Maternally derived H3.3 associates with the paternal chromatin, remains detectable in the nuclei until the morula stage, and is essential for correct transcription from the paternally derived chromosomes, the correct expression of the key pluripotency gene Oct4/Pou5f1 , and embryo preimplantation viability (Kong et al, 2018). This latter effect on Oct4/Pou5f1 suggests a possible long‐term maternal effect of oocyte‐derived H3.3 level on progeny phenotype.…”
Section: Oocyte Histones and Histone Modifiersmentioning
confidence: 99%
“…Although present in both sperm and egg, paternally derived H3.3 is lost after fertilization (Kong et al, 2018). Maternally derived H3.3 associates with the paternal chromatin, remains detectable in the nuclei until the morula stage, and is essential for correct transcription from the paternally derived chromosomes, the correct expression of the key pluripotency gene Oct4/Pou5f1 , and embryo preimplantation viability (Kong et al, 2018). This latter effect on Oct4/Pou5f1 suggests a possible long‐term maternal effect of oocyte‐derived H3.3 level on progeny phenotype.…”
Section: Oocyte Histones and Histone Modifiersmentioning
confidence: 99%
“…However, because there are only two genes for the histone H3.3 variant containing the S31 residue ( H3f3a and H3f3b ) we were able to target these genes by CRISPR. H3.3 is required for embryogenesis 2528 and spermatogenesis 29 . Further, as we find here (fig.…”
mentioning
confidence: 99%
“…This signal is normally obscured by maternally provided HIS-72 and HIS-74 , which is incorporated into paternal chromatin shortly after fertilization and prior to pronuclear fusion, but becomes visible when the H3.3::GFP fusions are only transmitted through the paternal germ line by sexual crossing of H3.3::GFP-carrying males to nontagged feminized hermaphrodites. These findings indicate that the H3.3 dynamics in nematodes differ slightly from mammalian systems, where paternally provided H3.3 is removed from the zygote with the second polar body and replaced by maternal copies of the histone ( Kong et al 2018 ). Moreover, it has been shown that epigenetic patterns established during worm spermatogenesis, including the ones associated with H3 and H3.3, are retained in the early embryo in C. elegans ( Arico et al 2011 ).…”
Section: Discussionmentioning
confidence: 94%